Raman effect and magnetic properties of doped TbMnO3 - Kumar A.; Shahi P.; Kumar S.; Shukla K.K.; Singh R.K.; Ghosh A.K.; Nigam A.K.; Chatterjee S. (My University, 2025)
The room temperature Raman scattering, structural and temperature variation of magnetic properties of Y- and Ni-doped TbMnO3 are investigated. Both for Y and Ni doping, the Néel temperature (TN) decreases. Y doping reduces effectively both the JTb-Tb and JMn-Mn exchange interactions, whereas Ni doping on the Mn site decreases only the JMn-Mn exchange interaction. The reduction in TN in the Ni-doped sample cannot be explained with simple exchange integral. It might be the case that Ni2+ doping changes the polarization flop observed in TbMnO3 which in effect may change the exchange interaction. In the room temperature Raman spectra for TbMnO3 and Y-doped TbMnO 3 eight modes are observed. When Ni is doped, modes due to MnO 6 bending and in-plane O2 stretching broaden and few modes disappear due to the induced lattice disorder. © 2013 IOP Publishing Ltd.